Inovasi Pendidikan Di Pesantren: Transformasi Dan Tantangan Di Era 5.0 - Afnita, Nora; Nofitayanti, Nofitayanti; Rahmadinur, Wisda; Pulungan, Dedi Zulkarnain; Effendi, Heri; Wandi, Joni Indra (Institut Agama Islam Sumatera Barat, 2023)
This research explores educational innovation in Islamic boarding schools (pesantren) and the challenges they face in the era of 5.0. Pesantren, as traditional educational institutions in Indonesia, have undergone significant changes in their efforts to remain relevant in an increasingly interconnected and modern world. In this context, the study takes a qualitative approach to understand how pesantren integrate technology, design integrated curricula, and adopt innovative teaching approaches to meet the demands of the 5.0 era. The research findings reveal that many pesantren have initiated the process of educational innovation. They have integrated digital technology into learning, designed integrated curricula with an emphasis on religious and general subjects, and adopted project-based learning approaches. This educational transformation aims to prepare students with 21st-century skills that are relevant, such as digital literacy, problem-solving, and creativity. However, the study also identifies several challenges faced by pesantren. Technology integration remains a hurdle, especially in rural areas where access and training are inadequate. Teacher training in the use of technology and innovative teaching methods is essential, and preserving traditional values while advancing education is a challenge that requires creative thinking. In conclusion, this research provides a comprehensive overview of the efforts of pesantren in educational innovation in the face of the 5.0 era. While there are challenges to be overcome, positive steps have been taken to ensure that pesantren remain relevant educational institutions in Indonesian society.